1988
DOI: 10.1590/s0006-87051988000100014
|View full text |Cite
|
Sign up to set email alerts
|

Arroz e trigo: tolerância à salinidade em solução nutritiva

Abstract: ( 3 ) Com bolsa de pesquisa do CNPq. RESUMOO estresse hídrico é uma das principais causas da baixa produtividade de grãos nas culturas de arroz e trigo-de-sequeiro no Brasil. Um programa de melhoramento genético usando um método para selecionar plantas tolerantes ao estresse hídrico diminuiria bastante esses efeitos negativos: por isso, tentou-se verificar os comportamentos de cultivares de arroz (sequeiro e irrigado) e trigo sob estresse salino considerando que estes se correlacionassem. Realizaram-se dois ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…From the results obtained in this experiment, for wheat seeds of cultivar IPR Catuara TM, it can be concluded that: Freitas and Camargo (1988) [16], working with four wheat cultivars IAC-5, IAS-55, Siete Cerros and Paraguay-281, analyzed the average weight of dry mass of seedlings, in relation to concentrations of 0; 100; 200; 300; 400 and 800 mmol L -1 NaCl in the substrate. At the 100 mmol L -1 dose of NaCl, the average dry weight increased for IAC-5, IAS-55 and Siete Cerros cultivars, and decreased for Paraguay-281.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…From the results obtained in this experiment, for wheat seeds of cultivar IPR Catuara TM, it can be concluded that: Freitas and Camargo (1988) [16], working with four wheat cultivars IAC-5, IAS-55, Siete Cerros and Paraguay-281, analyzed the average weight of dry mass of seedlings, in relation to concentrations of 0; 100; 200; 300; 400 and 800 mmol L -1 NaCl in the substrate. At the 100 mmol L -1 dose of NaCl, the average dry weight increased for IAC-5, IAS-55 and Siete Cerros cultivars, and decreased for Paraguay-281.…”
Section: Discussionmentioning
confidence: 85%
“…Freitas and Camargo (1988) [16], studying the saline effect on root length of four wheat cultivars, revealed lower mean lengths as salt doses (NaCl) increased. For concentrations of 0; 100; 200; 300; 400; and 800 mmol L -1 , the average root lengths were 154, 127, 66, 34, 20 and 20 mm, respectively.…”
Section: Germinationmentioning
confidence: 99%